The sound of two hands clapping : the education of a Tibetan Buddhist monk - Dreyfus, Georges B. J. (University of California Press, 2003)
A unique insider's account of day-to-day life inside a Tibetan monastery, 'The Sound of Two Hands Clapping' reveals to Western audiences the fascinating details of monastic education.